2013
DOI: 10.2298/jsc120505135s
|View full text |Cite
|
Sign up to set email alerts
|

Determination of trace elements in refined gold samples by inductively coupled plasma atomic emission spectrometry

Abstract: This paper presents a method for determination the trace contents of silver, copper, iron, palladium, zinc and platinum in refined gold samples. Simultaneous inductively coupled plasma atomic emission spectrometer with radial torch position and cross flow nebulizer was used for determination. In order to compare the different calibration strategies, two sets of calibration standards were prepared. The first set was based on matrix matched calibration standards and the second was prepared without the add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Therefore, it is clear that in the arsenal of analysts there must be simple and rapid methods to determine Au(III) in a wide concentration range with the highest possible sensitivity accuracy. Although many modern techniques, such as inductively coupled plasma atomic emission spectrometry (ICP-AES) [2], inductively coupled plasma mass spectrometry (ICP-MS) [3,4], electrothermal atomic absorption spectrophotometry (EAAS) [5,6], graphite furnace atomic absorption spectrophotometry (GFAAS) [7] are available for the determination of silver at trace levels in numerous complex materials.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is clear that in the arsenal of analysts there must be simple and rapid methods to determine Au(III) in a wide concentration range with the highest possible sensitivity accuracy. Although many modern techniques, such as inductively coupled plasma atomic emission spectrometry (ICP-AES) [2], inductively coupled plasma mass spectrometry (ICP-MS) [3,4], electrothermal atomic absorption spectrophotometry (EAAS) [5,6], graphite furnace atomic absorption spectrophotometry (GFAAS) [7] are available for the determination of silver at trace levels in numerous complex materials.…”
Section: Introductionmentioning
confidence: 99%
“…These interferences are often reported to result in systematic and random errors, which eventually cause loss of accuracy and precision [4]. Research has shown that the most frequently used calibration method, namely direct calibration or 'straight run' in spectrometric analysis is severely affected by these interferences [5]. Different spectrometric methods have been developed in the past few years in an attempt to reduce or correct for these numerous matrix effects in spectrometric analysis.…”
Section: Introductionmentioning
confidence: 99%